"What's Your Taste in Music?" A Comparison of the Effectiveness of Various Soundscapes in Evoking Specific Tastes. (24th December 2015) - Wang, Qian (Janice); Woods, Andy T.; Spence, Charles
We report on the results of two online experiments designed to compare different soundtracks that had been composed (by various researchers and sound designers) in order to evoke/match different basic tastes. In Experiment 1, 100 participants listened to samples from 24 soundtracks and chose the taste (sweet, sour, salty, or bitter) that best matched each sample. Overall, the sweet soundtracks most effectively evoked the taste intended by the composer (participants chose sweet 56.9% of the time for the sweet soundtracks), whereas the bitter soundtracks were the least effective (participants chose bitter 31.4% of the time for the bitter soundtracks), compared with chance (choosing any specific taste 25% of the time). In Experiment 2, 50 participants rated their emotional responses (in terms of pleasantness and arousal) to the same 24 soundtrack samples and also to imaginary sweet/sour/salty/bitter-tasting foods. Associations between soundtracks and tastes were partly mediated by pleasantness for the sweet and bitter tastes and partly by arousal for the sour tastes. These results demonstrate how emotion mediation may be an additional mechanism behind sound-taste correspondences.